Bisphosphonates Versus Denosumab for Prevention of Pathological Fracture in Advanced Cancers With Bone Metastasis: A Meta-analysis of Randomized Controlled Trials. (August 2020) - Al Farii, Humaid; Frazer, Abbey; Farahdel, Leila; AlFayyadh, Faisal; Turcotte, Robert
Abstract : Background: Metastasis to the bone is one of the most common complications associated with advanced cancer. Patients with bone metastases are at risk of devastating skeletal related events, including pathological fractures. Purpose: The aim of this study was to analyze the efficacy of zoledronic acid (ZA) versus denosumab in the prevention of pathological fractures in patients with bone metastases from advanced cancers by evaluating all available randomized controlled trials (RCTs) on this subject. Methods: A systematic search of electronic databases (PubMed and MEDLINE) was performed to identify all published RCTs comparing ZA with denosumab in prevention of pathological fractures in bone metastases. Risk of bias of the studies was assessed. The primary outcomes evaluated were pathological fractures. Results: Four RCTs (7, 320 patients) were included. Denosumab was superior to ZA in reducing the likelihood of pathological fractures, when all tumor types were combined (odds ratio [OR] 0.86, 95% confidence interval [CI], 0.74 to 0.99, P = 0.04). Denosumab was favored, although not statistically significant, over ZA in endodermal origin (breast and prostate) (OR 0.85, 95% CI, 0.68 to 1.05, P = 0.13) and mesodermal origin tumors (solid tumors and multiple myeloma) (OR 0.87, 95% CI, 0.71 to 1.06, P = 0.16). Discussion: Denosumab moderately reduces the likelihood of pathological fractures in comparison to ZA in patients with bone metastases with statistical significance. When pathological fractures were grouped by tumor origin (endodermal or mesodermal), no statistical difference was observed between denosumab and ZA. Further long-term studies are needed to confirm the effectiveness of these treatment regimens.